Differences in Importance Attached to Drug Effects Between Patients With Type 2 Diabetes From the Netherlands and Turkey: A Preference Study - Roldan Munoz, Sonia; Postmus, Douwe; de Vries, Sieta T.; Arnardottir, Arna H.; Dolu, İlknur and Hillege, Hans and Mol, Peter G. M. (Frontiers in Pharmacology, 2021)
Objective: The aim of this study was to compare the importance that patients with type 2 diabetes mellitus from the Netherlands and Turkey attach to certain drug effects of oral anti-diabetic drugs. Methods: Data were collected through a cross-sectional survey containing demographic questions and a discrete choice experiment assessing preferences for oral anti-diabetic drugs. Adults from the Netherlands and Turkey were included if they had type 2 diabetes mellitus and had received a prescription of an oral anti-diabetic drug in the last 4 months. The oral anti-diabetic drugs in the discrete choice experiment were described in terms of six attributes: effects on HbA1c, cardiovascular diseases, weight change, gastrointestinal adverse drug events hypoglycemic events, and bladder cancer. Multinomial logit models with country as an interaction factor were fitted. Results: In total, 381 patients were included, 199 from the Netherlands and 182 from Turkey. Patients’ preferences towards drug effects varied between the countries. Turkish patients attached the highest importance to reducing the risk of cardiovascular diseases (relative weight: 0.51, 95% CI 0.45-0.55), followed by reducing hypoglycemic events (relative weight: 0.16, 95% CI 0.11-0.22), and reducing gastrointestinal adverse drug events (relative weight: 0.11, 95% CI 0.07-0.18). Patients from the Netherlands attached the highest importance to gastrointestinal ADEs (relative weight: 0.22, 95% CI 0.14-0.39), followed by reducing hypoglycemic events (relative weight: 0.22, 95% CI 0.16-0.25), and reducing the risk of cardiovascular diseases (relative weight: 0.20, 95% CI 0.13-0.23). Conclusions: Patient preferences may differ across countries. Such differences should be acknowledged in regulatory decisions and clinical practice.